Anaesthesia, pain and recovery profiles in children following dental extractions. Issue 4 (July 2020) - Akl, Natalie; Sommerfield, Aine; Slevin, Lliana; Drake-Brockman, Thomas FE; Wong, Susan; Winters, John C; Ungern-Sternberg, Britta S von; Sommerfield, David
The aim of this prospective cohort study was to describe the anaesthetic practices, rates of postoperative pain and the recovery trajectory of children having urgent dental extractions at our institution. Demographic, anaesthetic and surgical details of children undergoing dental extractions were obtained by case note review. Parent-proxy pain scores were collected via telephone on the day of surgery and on postoperative days, as well as details of analgesia given, behavioural disturbance, and nausea and vomiting. Follow-up was continued until each child no longer had pain. Datasets were analysed for 143 patients. Fasting times were prolonged, with 81 children (56.6%) fasted for over four hours from fluids. Moderate or severe pain was recorded in 14 children (9.8%) postoperatively on the day of surgery, with higher rates in children who had a greater number of teeth extracted. Low rates of moderate to severe pain were observed during follow-up, affecting six children (4.2%) on postoperative day 1 and three children (2.1%) on postoperative day 2 with primarily simple analgesia administered at home. Only eight children (5.6%) had nausea and/or vomiting on the day of surgery. Rates of reported behavioural disturbance at home were low, extending beyond the second postoperative day in only two children (1.4%), and only four children (2.8%) attended a dentist during the follow-up period. In conclusion, the low rates of pain and nausea and vomiting reported in the days following surgery for urgent dental procedures suggest that children can be cared for at home with simple analgesia.